THE INFLUENCE OF PRICE DISCOUNT AND STORE IMAGE TOWARD CONSUMER PURCHASE INTENTION (CASE STUDY IN FRESHMART SUPERSTORE BAHU MANADO) - Supardi, Oey Rebecca Gabriella (Sam Ratulangi University, 2015)
ABSTRACT Price Discount has a negative influence on perceptions of quality. Perceptions of quality can be explained using self perception theory, one type of attribution theory which describes how consumers explain events. If a consumer purchases a product on discount they often